Development of Motion Graphic Video (MGV) Based Nutrition Education Media for Young Women to Prevent Anemia - Maya Amini; Ai Nurhayati; Atat Siti Nurani (Media Pendidikan Gizi dan Kuliner, 2022)
Adolescent girls are one of the groups that are prone to anemia. Therefore, to increase the knowledge of young women, nutrition education is held. The media used for nutrition education is motion graphic video. Motion graphics are an alternative to video shows that are widely used by the media. Media with motion graphics was chosen as one of the effective and interesting educational media because of the combination of text, pictures, colors, sound, in conveying messages about anemia and explaining food ingredients that can prevent anemia. This study aims to produce nutritional education media based on motion graphic videos for young women to prevent anemia. The development process uses the Research and Development (RD) model. D) the lowest (level 1) to produce a design but not proceed with field testing. The instruments used in this research include storyboard motion graphic video validation sheets and motion graphic video media validation sheets. The results of the validation of nutrition education media based on motion graphic videos by material experts are seen from the aspects of content and language, namely with an overall score of 3 with appropriate criteria and with conclusions the media can be used. While the results of the validation of nutrition education media based on motion graphic video by media experts, namely the score on the audio aspect is 3 with appropriate criteria and the score on the visual aspect is given an average score of 3 with appropriate criteria.